Pendekatan Per Se Illegal dan Rule Of Reason dalam Hukum Persaingan Usaha di Indonesia - Supianto Supianto (JURNAL RECHTENS, 2013)
In the competition law recognized the existence of several approaches in the application of the law, two of which approach is the approach per se illegal and rule of reason approach. Approach per se illegal and rule of reason applied to assess whether a particular course of business actors violating Competition Act. Restrictions are per se is the prohibition is absolute, clear and obvious to a particular act or agreement to provide certainty to businesses. An act or agreement that prohibited per se means certain that such actions would impair or eliminate competition. Instead the approach is a rule of reason, an act which is done by the business will be seen the extent of the negative impact on competition climate. The second method has a different approach is also used in competition law in Indonesia.